Khotbah yang “Diurapi” oleh Roh Kudus - Amos Winarto Oei (Veritas : Jurnal Teologi dan Pelayanan, 2017)
On the one hand, every preacher who desires to experience the power of the Holy Spirit in the sermon will struggle to see “the anointing” of the Spirit. On the other, there are preachers who even afraid of experiencing that power in their sermon. What is a Spirit-anointed sermon? Why also are there preachers who are even afraid of that anointing power? And how does a preacher nurture his/her faith in the Holy Spirit to empower a sermon? This article attempts to answer those question.